How to use noninvasive positive airway pressure device data reports to guide clinical care. Issue 1 (31st October 2019) - Perrem, Lucy; Mehta, Kevan; Syed, Faiza; Baker, Adele; Amin, Reshma
Abstract: There has been a significant increase in the past few decades in the number of children receiving noninvasive positive airway pressure (PAP) therapy at home. At present, PAP therapy can be successfully used in children of all ages, for a variety of indications. Data acquired from PAP devices is clinically useful, providing objective information regarding adherence, leak, and efficacy of PAP therapy. However, guidelines outlining a standardized approach to interpretation of PAP device data in pediatrics is currently lacking. Given the rapidly expanding use of PAP therapy in pediatric practice, we aim to provide an overview of the interpretation of data reports, otherwise called "data downloads, " from PAP devices and illustrate how they can be used to guide clinical care.